Massive Migration and its Effect on Human Capital and Growth: The Case of Western Balkan and Central and Eastern European Countries - Michael Landesmann; Isilda Mara (The Vienna Institute for International Economic Studies (wiiw), 2016)
We analyse the effect of massive migration particularly from the Western Balkans and the Central and Eastern European countries on human capital and growth. In our analysis, we use a system of three equations to estimate simultaneously the effect of migration on human capital and on growth. An important driver of migration is chain migration, as well as the unemployment and income differentials between developing and developed countries. Overall, our findings suggest that migration of highly skilled from the Western Balkan and Central Eastern European countries has been beneficial to economic growth and income convergence of these countries. Our analysis supports the positive impact of low-skilled migration on the composition of human capital in the source countries.
Keywords: F22; J24; O15; O40; 330; migration; brain drain; brain gain; economic growth; human capital